2020
DOI: 10.3390/ijerph17218095
|View full text |Cite
|
Sign up to set email alerts
|

Manual Material Handling Training: The Effect of Self-Observation, Hetero-Observational and Intrinsic Feedback on Workers’ Knowledge and Behaviour

Abstract: This study aimed to assess the effect of systematic self-observation, hetero-observational feedback, and feedforward and intrinsic feedback (SsObserWork components) on workers’ knowledge and behaviour of a manual material handling (MMH) technique in the industrial sector. Blue-collar workers recruited from a food processing company in Catalonia (Spain) were randomized into SsObserWork (N = 31) and control (N = 30) groups. SsObserWork group members participated individually in two sessions and a three-week foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…(56 topics). Examples: • Stretching, strengthening or relaxing exercises • Warm-up routines • Posture correction exercises [ 26 ]; [ 27 , 85 ]; [ 28 ]; [ 31 ]; [ 34 ]; [ 23 ]; [ 76 ]; [ 24 ]; [ 86 ]; [ 77 ]; [ 38 ]; [ 39 ]; [ 41 ]; [ 87 ]; [ 46 ]; [ 47 ]; [ 52 ]; [ 53 ]; [ 62 ]; [ 64 ]; [ 88 ]; [ 65 ]; [ 66 ]; [ 68 ]; [ 69 ]; [ 70 ]; [ 89 ]; [ 90 ]. 4.…”
Section: Resultsmentioning
confidence: 99%
“…(56 topics). Examples: • Stretching, strengthening or relaxing exercises • Warm-up routines • Posture correction exercises [ 26 ]; [ 27 , 85 ]; [ 28 ]; [ 31 ]; [ 34 ]; [ 23 ]; [ 76 ]; [ 24 ]; [ 86 ]; [ 77 ]; [ 38 ]; [ 39 ]; [ 41 ]; [ 87 ]; [ 46 ]; [ 47 ]; [ 52 ]; [ 53 ]; [ 62 ]; [ 64 ]; [ 88 ]; [ 65 ]; [ 66 ]; [ 68 ]; [ 69 ]; [ 70 ]; [ 89 ]; [ 90 ]. 4.…”
Section: Resultsmentioning
confidence: 99%
“…Park and Lee say that basketball is the top game loved by audiences all over the world, so there must be more personalized and perfect requirements for athletes' basic physical ability and technical and tactical level in training [ 2 ]. Sene-Mir et al said that according to the definition of Chinese experts, physical training ability refers to the improvement of athletes' technical level and tactical level, which is reflected in three aspects, including basic physical ability, good physical quality, and technical and tactical level, which is based on the ability to create excellent competition results [ 3 ]. Lee et al say that the development of physical ability will be one of the key factors in the ultimate success and provide a strong athletic life [ 4 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some authors have argued that in order for a multisource evaluation to be successful, the quality feedback it produces must be used to design an intervention plan for improving performance. This, the authors argue, most faithfully represents the original intent of the 360 • MSF model [22,28]. Most of the existing studies apply transversal designs, preventing an analysis of the sensitivity to change after an intervention or an assessment of the factors that influence an intervention's effectiveness.…”
Section: Introductionmentioning
confidence: 76%
“…Most of the existing studies apply transversal designs, preventing an analysis of the sensitivity to change after an intervention or an assessment of the factors that influence an intervention's effectiveness. A few studies, such as the Physician Assessment Review (PAR), the Sheffield Peer Review Assessment Tool (SPRAT) [28][29][30][31], or some developed for assessing nursing students [19], or anesthesia residents [20], present a longitudinal design, but in the best of cases, only the intention to change is analyzed [9,[32][33][34][35][36][37][38]. Even studies that have reported improved performance over time recognize that the behavioral change produced may not be entirely attributable to the feedback provided [29].…”
Section: Introductionmentioning
confidence: 99%